Stability of Early Maturing Soybean Genotypes in Poland - Danuta Kurasiak-Popowska; Agnieszka Katańska-Kaczmarek; Przemysław Matysik; Piotr Stefański; Patrycja Przybył; Ewa Skotarczak; Jerzy Nawracała (Agriculture)
Poland is one of the northernmost countries in the world where soybean breeding is actively conducted. A large collection of soybean genotypes was analyzed in three locations in Poland during the 2022–2023 growing seasons. The objective of this research was to determine the stability of yield, as well as the protein and fat content in the seeds of 280 genotypes. The phenotypic correlations across genotypes and environments were assessed using the Spearman coefficient. The statistical analysis was provided using the additive main effects and multiplicative interaction model. The stability of genotypes was assessed using the weighted average of absolute scores. The main factor differentiating the results between locations was the variation in weather conditions. The variety Karok, which ranks among the top 10% in genotype selection indices for yield and thousand-seed weight, is recommended based on studies conducted within the Post-Registration Variety Testing System in three voivodeships in Poland. Among the most stable genotypes, in terms of the traits analyzed in this paper, are many registered and currently grown soybean varieties such as Obelix Pompei, Coraline, Kapral, ES Mentor, NS Mercury, Pepita, Pollux, Silesia, and Heihe 45. The yield stability of soybean genotypes during the development of new varieties should be one of the factors analyzed by breeders.